Value Engineering Implementation In The River Sentiong Normalization Project, Jakarta Central - Dinariana, Dwi; Jayady, Arman; Daeroby, Achmad (Green Publisher Indonesia, 2023)
In Central Jakarta, work to normalize times every year is carried out but the available budget is insufficient to accommodate all proposals for normalization every year. This research aims to optimize the use of the budget in public works infrastructure in Central Jakarta through the application of the value engineering (VE) method. The focus is on the Sentiong River Normalization Project by finding the best creative ideas using VE. The Value Engineering method consists of seven stages, including function analysis, evaluation, and recommendations. Primary data was obtained through interviews, while secondary data was in the form of Budget Plans and literature studies. The results showed that by replacing the previous design using concrete sheet piles, it was possible to achieve a cost savings of 15.61% in a 50 year construction period.